Status of anthelmintic resistance in gastrointestinal nematodes of sheep in Rajasthan* - MAHARSHI, A K; SWARNKAR, C P; SINGH, D; MANOHAR, G S; AYUB, M (The Indian Journal of Animal Sciences, 2011)
A study was conducted to assess the status of anthelmintic resistance in gastrointestinal nematodes (predominantly Haemonchus contortus) of sheep maintained at organized farms and farmer’s field in Rajasthan through in-vivo faecal egg count reduction test and in-vitro egg hatch assay. The magnitude of reduction in the faecal egg counts by fenbendazole (@ 5.0 mg kg-1 body weight) revealed emergence of benzimidazole resistance in H. contortus of sheep from all the farm and field flocks except in field flocks from north-eastern Rajasthan where 66.7% flocks possessed benzimidazoleresistant H. contortus. With tetramisole (@ 15 mg kg-1 body weight) resistance in H. contortus was observed in farm flock of north-eastern region whereas among field flocks it ranged from 33.33% (north region) to 83.33% (eastern region). On egg hatch assay, strains of worms were found susceptible to benzimidazole in farm flocks of northern region while in field flocks prevalence of benzimidazole resistance strongyle worms was 100% in eastern and northern region and 83.33% in north-eastern region. A high agreement (86.4%) with poor linear correlation (r = 0.087) was observed between results of both faecal egg count reduction test and egg hatch assay for benzimidazole resistance.